PENGARUH MODUL HIPERTENSI BERBASIS MODEL IMB (INFORMATION, MOTIVATION, AND BEHAVIORAL SKILL) DALAM MENINGKATKAN KEPATUHAN MINUM OBAT PADA PASIEN HIPERTENSI - Jean Surinala Sitepu (SUAN PUBLISHER, 2025)
Medication adherence is a critical determinant in the successful management of hypertension, yet it remains significantly low in Indonesia, leading to increased risks of cardiovascular complications. This study aims to evaluate the effectiveness of an educational intervention using a Hypertension Module based on the Information, Motivation, and Behavioral Skills (IMB) model in improving medication adherence among primary hypertension patients. A quasi-experimental research design with a non-equivalent control group was employed. The sample included [Insert Number] participants, divided into an intervention group and a control group. Data were collected using the 8-item Morisky Medication Adherence Scale (MMAS-8) and clinical blood pressure measurements. Statistical analyses were performed using Paired T-Tests and Independent T-Tests. The results demonstrated a significant increase in medication adherence scores within the intervention group following the module's implementation (p < 0.05), which correlated with improved blood pressure control. In contrast, the control group showed no substantial change in adherence behavior. The findings indicate that integrating information, personal/social motivation, and practical behavioral skills within a structured module effectively enhances patients' self-efficacy and long-term treatment management. This study concludes that the IMB-based module is a superior educational tool compared to conventional verbal education. It is recommended that primary healthcare facilities adopt this model-based module as a standardized part of chronic disease management programs to reduce hypertension-related morbidity and mortality